THE ROLE OF TRANSLATION IN TEACHING THE GERMAN LANGUAGE (SITUATION IN ALBANIA) (PALIMPSEST / ПАЛИМПСЕСТ, 2026)
In the long history of foreign language teaching, translation is one of the most discussed activities. In this context, and in order to gain a comprehensive overview of the actual situation regarding the role and use of translation as a didactic tool in German language teaching in Albania, a fifteen-question questionnaire was developed and addressed to German language teachers. This served as a research instrument to collect empirical data regarding the perceptions and experiences of German language teachers. The goal was to determine with which age groups and at which language levels German language teachers use translation in their lessons, how they conceptualize it, what challenges they face in doing so, and what support they consider necessary. Furthermore, it was very important to understand whether translation in foreign language teaching is used simply as a means of grammatical comparison and vocabulary building, or whether teachers also aim to promote learners' sensitivity to cultural elements, their ability to understand problems, and the development of new learning strategies. The study follows a mixed-method approach: a quantitative approach to identify key trends in the use of translation and a qualitative approach to explain the reasons and perceptions behind these trends. This combination provides a more comprehensive picture of the role of translation in German language teaching in Albania. This article also offers teachers recommendations regarding the forms and methods of using translation in German language teaching, from selecting a goal-oriented task to developing analytical skills regarding the function, content, and form of linguistic phenomena in the source language.
Keywords: translation; foreign language teaching; GMT; vocabulary building; cultural elements.